Retinal nerve fiber layer and ganglion cell layer changes on optical coherence tomography in early multiple sclerosis and optic neuritis cases - Pillay, Ganesh (Indian J Ophthalmol, 2018)
PURPOSE: To study the retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) changes on optical coherence tomography in early multiple sclerosis (MS) patients. METHODS: A prospective cohort study was conducted at a tertiary care center. Patients of early MS (expanded disability status scale <3) with or without optic neuritis (ON) and idiopathic ON were included. Twenty age-matched individuals were taken as controls. Changes in RNFL and GCL thickness were evaluated along with the correlation with visual function parameters such as visual acuity, contrast sensitivity, and visual evoked response at first visit and again at six months. RESULTS: Forty-four patients of MS with or without ON (24 and 20 patients respectively), 29 patients with idiopathic ON, and 20 healthy controls constituted the cohorts. Mean LogMAR best-corrected visual acuity was found to be significantly reduced in all groups except fellow eyes (FE) of ON group. Mean values of average RNFL thickness and values in superior, temporal, and inferior quadrant were significantly reduced. Similarly, overall mean values of average GCL-inner plexiform layer (IPL) thickness and values in superior, superonasal, superotemporal, inferonasal, and inferotemporal quadrant were significantly reduced in all groups except FE of ON group (P < 0.05). All the visual parameters significantly correlated with GCL + IPL thickness. CONCLUSION: GCL + IPL thickness is a more sensitive clinical structural marker than RNFL in early MS with/without ON and ON patients and correlates with all the visual parameters better than RNFL thickness.